Follicular Dynamics and Hormonal Regulation during Physiologic Breeding Season in Cyclic Mare - Nyaupane, Nirvik (Journal of Agriculture and Forestry University, 2026)
This review synthesizes published information regarding equine follicular dynamics and endocrine regulation throughout the normal estrus cycle with a particular focus on follicular emergence, deviation, dominant follicle selection, preovulatory maturation, and ovulation. Literature was compiled from peer-reviewed journal articles, reviews, and equine reproduction textbooks concerning ovarian follicular development and hormonal regulation in mares during the breeding season. Available evidence suggests that there is a transient surge in follicle stimulating hormone (FSH) driving a cohort of 6 mm follicles to grow together at roughly 2.8 mm daily prior to the onset of deviation occurring when the largest follicle reaches 22 mm in major follicular waves, which is followed by a decrease in circulating FSH and an increase in intrafollicular insulin-like growth factor (IGF-1) activity, estradiol, inhibin, and luteinizing hormone (LH) responsiveness. The next steps of maturation of the dominant follicle (growing at rate of 3mm per day), competency of the ovulatory follicle (reaching a plateau of approximately 40-45mm) and induction of ovulation involve a coordinated interplay of gonadotropins, ovarian steroids and local intraovarian mediators. An understanding of these physiologic interactions is of direct clinical importance in the fields of estrus detection, timing of ovulation, reproductive ultrasonography, breeding management, and clinical decision making in the field of equine theriogenology.